Analysis of the competitive weekly microcycle in elite soccer: comparison of workload behavior in absolute and relative terms - Guerrero-Calderón, B.; Fradua, L.; Morcillo, J. A.; Castillo-Rodríguez, A. (The Journal of Strength and Conditioning Research, 2023)
This study aimed to analyze the locomotion activity of elite-level soccer players throughout the weekly microcycle by playing position, and compare the training-load (TL) behavior in relation to match-play in absolute and relative (meters or events per minute) terms. Training and match data were collected from 30 professional soccer players belonging to a Spanish First Division team during the 2015/2016 season using global positioning technology (152 training sessions and 38 matches). Overall, the results showed a decrease of TL metrics when competition approached (p < 0.05). However, a progressive decrease was not found for all metrics. Two-way analysis of variance test revealed that workload was affected by the interaction between microcycle-day and season period showing medium or large effect size (partial Eta square > 0.15) for all positions and metrics. Considering the TL in relation to the match-load, opposite load behavior was found in absolute and relative terms by position; whereas, central-defenders, external-defenders, and forwards covered 21, 25 and 26% more absolute medium-speed running distance (MSRD), respectively; central-defenders covered 14% (8.6-13.4 m/min), external-defenders 10% (7.5-13.9 m/min), and forwards 7% (8.4-15.7 m/min) more relative-MSRD 4 days before match than match-day. The accelerations-metric also showed higher relative values 4, 3, and 2 days before the match. Because the objective of the training is to prepare players to withstand the competition demands, analyzing the position-specific TL concerning to match demands represents an advantageous strategy for training periodization. In addition, this study highlights the importance of taking into account the time spent of developing the different efforts to properly define the position-specific physical demands.